GIA modelling of Greenland using an ice history from the last glacial cycle to present day with lateral varying viscosity profiles on a spherical Earth - Faure, Nils (author) (2022)
Glacial Isostatic Adjustment (GIA) is a process which focuses on the deformations of the Earth due to changing ice sheets. It is an important study in Climate Sciences, gravimetric studies and Earth modelling. Studying GIA allows to contribute to a better understanding of the Earth’s composition, thanks to the testing of multiple Earth models, as well as a broader understanding of the Earth’s ice age cycles. In GIA research, spherical Earth models have been used for half a century. However, 3D Earth models distinguish themselves by using a 3D varying viscosity profile. The reason for this recent interest is that little is known with precision about the Earth’s mantle and deeper layers structure and that such a model was more difficult to create; the inclusion of three dimensional (3D) varying viscosity profiles have not yet been widely used in GIA studies in Greenland. Hence, to this day and to our knowledge, only two papers have made use of a laterally varying viscosity in order to study GIA in Greenland: Milne et al. (2018) and van der Wal and Xu, (2016). The first novelty introduced by this Master Thesis is the use of the Olivine flow viscosity model, with a wet rheology, to study GIA in Greenland. The second main novelty in this Master Thesis, is the use of a unified ice history from 122000 years from present till 2019 in one GIA model; while using a resolution of 10 [𝑘𝑚], which is an improvement, compared to for instance Milne et al. (2018), Simpson et al. (2011) or Lecavalier et al. (2014) which use resolutions ranging from 15 to 75 [𝑘𝑚], which is found to still not be sufficient enough to properly model modern elastic and viscous deformation. The following conclusions were made through analysing the final results. First, the simulations which use 3D viscosity models are more sensitive regionally and react, to ice load changes with larger amplitudes of solid Earth deflections in shorter time spans. Second, 3D varying viscosity models, with the same ice loads ...